The effect of fatigue on strength-power tests for distinguishing elite-level male kickboxers - Ozbay, Serhat; Gencoglu, Cebrail; Ulupinar, Sueleyman; Cinar, Vedat; Ouergui, Ibrahim; Holbling, Dominik (Sage Publications Inc, 2025)
BACKGROUND: Based on recent research, slight performance differences, particularly dependent on the state of recovery, might be crucial for tournament success among elite-caliber kickboxers. OBJECTIVE: This study aims to; a) determine which strength-power tests could discriminate better between elite and top-elite kickboxers and, b) to evaluate changes in testing results between fatigued and well-rested athletes. METHODS: Twenty-two international kickboxers (including World and European Champions) volunteered to participate in this study. Nine kickboxers were assigned to the top-elite group and 13 to the elite group based on their highest tournament achievements. Subjects performed the Wingate test (Win) for anaerobic power; countermovement jump (CMJ) and squat jump (SJ) for neuromuscular power; push-ups and pull-ups for strength endurance; squats (SQ) and bench press (BP) for maximal dynamic strength; handgrip, leg, and back strength for isometric strength after full rest, following the fatigue and advanced fatigue protocols. RESULTS: Discriminant function analysis correctly classified the groups at 60.5%, 75.3%, and 86.3% in the resting, fatigue, and advanced fatigue protocols, respectively. Furthermore, all strength-power performances have significantly decreased and lactate(peak) increased (p < 0.05) after the fatigue and advanced fatigue protocols in both groups. Significant interaction were also observed in the Win(peak) (p < 0.001, eta(2)(p) = 0.559), Win(mean) (p = 0.009, eta(2)(p) = 0.246), CMJ ( p = 0.010, eta(2)(p) = 0.273), push-ups (p < 0.001, eta(2)(p) = 0.389), SQ(absolute) (p = 0.001, eta(2)(p) = 0.337), BPabsolute ( = 0.014, eta(2)(p) = 0.235) and, Lactate(peak) (p = 0.026, eta(2)(p) = 0.220). CONCLUSION: Resistance to fatigue may be the key component for distinguishing elite-level athletes. Thus, strength-power tests should be performed following a certain level of fatigue for the elite athletes due to distinguish them more effectively.
Keywords: Kickboxing; strength-power tests; strength performance; performance decrease; Wingate